Ð˜Ð·ÑƒÑ‡ÐµÐ½Ð¸Ðµ Ð²Ð»Ð¸ÑÐ½Ð¸Ñ ÑÐºÑÑ‚Ñ€Ð°ÐºÑ‚Ð° Ð¿Ð»Ð°Ñ†ÐµÐ½Ñ‚Ñ‹ Ð¸ Ð½ÐµÐ¹Ñ€Ð¾Ñ‚ÐºÐ°Ð½Ð¸ Ð½Ð° Ð¼ÐµÐ¼Ð±Ñ€Ð°Ð½Ð¾-Ð¼ÐµÑ‚Ð°Ð±Ð¾Ð»Ð¸Ñ‡ÐµÑÐºÑƒÑŽ Ñ„ÑƒÐ½ÐºÑ†Ð¸ÑŽ Ð¼Ð¸Ñ‚Ð¾Ñ…Ð¾Ð½Ð´Ñ€Ð¸Ð¹ Ð¸ Ð¼Ð¸ÐºÑ€Ð¾ÑÐ¾Ð¼ Ð¸Ð· Ð¿ÐµÑ‡ÐµÐ½Ð¸ ÐºÑ€Ñ‹Ñ Ð² ÑÐ¸ÑÑ‚ÐµÐ¼Ðµ in vitro - Strona, V. I.; Yurchenko, T. N.; Ryazantsev, V. V.; Shepitko, V. I.; Prokopyuk, O. S.; Gordienko, A. I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2002)
In the models of enzymic ascorbate-dependent lipid peroxidation (LPO) of microsomes and using the estimation of metabolic state of rat’s liver mitochondriaa in vitro the authors have studied antioxidative properties of placenta and neurotissue preparations. Existing cryotechnology of obtaining and storage of biopreparations based on placenta and nerve tisue provides a high content of.